A preliminary validation of the impact on participation and autonomy questionnaire in an Iranian sample of patients with type 2 diabetes - Reza Vazirinejad; Mohammad Ali Zakeri; Hassan Ahmadinia; Sayed Mortaza Hossini Rafsanjanipoor (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: This study aimed to determine the face, convergent validity, internal consistency, and stability reliability of the impact on participation and autonomy-Persian version (IPA-p) scale for using among Iranian patients with type 2 diabetes. MATERIALS AND METHODS: Trained experts interviewed 227 type 2 diabetes patients who were registered in out-patient Diabetes Clinic of Ali-Ibn Abi-Talib Hospital, (Rafsanjan, Southeast Iran from May 2018 to February 2019) and their relatives to assess the face and convergent validity, internal consistency, and stability reliability of the IPA-p scale. A checklist was used to collect demographic information and also to record expert's̛̛̛̛̛̛ points of view about the scale to assess face validity. Internal consistency was measured using Cronbach's alpha, and stability was assessed using interclass correlation coefficients (ICCs). Test-retest method was used to detect the reliability of the questionnaire. Respondents completed the IPA-p scale on the two occasions with an interval of 30-45 days. RESULTS: In relation to convergent validity, the confirmatory model showed an acceptable fit and the scale had a highly convergent validity. Exploratory factor analysis showed that the IPA-p scale has a ten-factor structure that explained 77.42% of the variance. Cronbach's alpha between the mean IPA-p scores achieved on the two occasions ranged from 0.65 to 0.92. Test-retest ICCs for the ten domains were between 0.64 and 0.81. CONCLUSIONS: The IPA-p questionnaire can be a relatively valid and reliable instrument for assessing self-reported participation among Iranian type 2 diabetes patients. However, some improvement is needed to make it fully suitable for using among Persian-language diabetic patients.